1995
DOI: 10.1038/sj.bdj.4808944
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation counselling--a role for the dental profession?

Abstract: Whilst several studies have investigated the views of North American dentists on providing advice to patients on stopping smoking, the role of their UK counterparts in this area is uncertain. Thus this study aimed: 1. to examine dentists' awareness of the effect of smoking on general and oral health, 2. to determine their views on counselling patients to give up smoking, 3. to investigate the extent to which they currently engage in this activity, and 4. to survey barriers to providing such advice. Data were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 0 publications
5
61
0
Order By: Relevance
“…3,[17][18][19] This practice has not always been reported by UK dentists -only 6% of Scottish dentists always recorded smoking history and 35% never did. 20 There was more variation among students in advising patients to stop smoking. Recommendations for health care professionals are that all smokers be advised to quit, 17 and the study reported here does not refl ect this.…”
Section: Discussionmentioning
confidence: 99%
“…3,[17][18][19] This practice has not always been reported by UK dentists -only 6% of Scottish dentists always recorded smoking history and 35% never did. 20 There was more variation among students in advising patients to stop smoking. Recommendations for health care professionals are that all smokers be advised to quit, 17 and the study reported here does not refl ect this.…”
Section: Discussionmentioning
confidence: 99%
“…Other effects of smoking are not as visible and tangible as the oral effects. 3,10 Dentists should not hesitate to give smoking advice to their patients and grasp this opportunity to improve the oral and general health of the community.…”
Section: Discussionmentioning
confidence: 99%
“…Early 9,10 and more recent studies 11 found that the percentage of dentists involved in smoking cessation was considerably lower than those who felt they had a role to play in such activity. However, involvement is increasing.…”
Section: N B R I E Fmentioning
confidence: 97%
“…12,13 Frequently reported barriers to being involved in smoking cessation include pressures of time and finance. 9,13,14 Lack of training and possible adverse effects on the dentist-patient relationship have been identified as barriers for both smoking cessation 9,10,14 and inquiring on alcohol consumption. 12 A similar trend has been reported for involvement in blood pressure monitoring.…”
Section: N B R I E Fmentioning
confidence: 99%